Long-term survival in a patient with glioblastoma on antipsychotic therapy for schizophrenia: a case report and literature review - Shahdabul Faraz; Susan Pannullo; Marc Rosenblum; Andrew Smith; A. Gabriella Wernicke (Therapeutic Advances in Medical Oncology, 2016)
Glioblastoma is not only the most common primary brain tumor, but also the most aggressive. Currently, the most effective treatment of surgery, chemotherapy and radiation therapy allows for a modest median survival of 15 months. Here, we report a case of a 57-year-old male with histologically confirmed glioblastoma with unfavorable prognostic characteristics (poor performance status and persistent neurological symptoms after surgery), whose expected 5-year survival is 0%. Further genetic analysis offered a mixed prognostic picture with positive methylation of 0-6-methylguinine-DNA (deoxyribonucleic acid) methyltransferase (MGMT; favorable prognosis) and wild-type isocitrate dehydrogenase 1 (IDH-1; unfavorable prognosis). Remarkably, the patient showed a progression-free survival of 5.5 years and a total survival of 6.5 years. In the context of recently published literature, the authors hypothesize that the patient’s use of the antipsychotic medication risperidone may have had a potential antitumor effect. Risperidone antagonizes the dopamine-2 receptor and the serotonin-7 receptor, both of which have been individually implicated in the growth and progression of glioblastoma. To the authors’ knowledge, this is the first clinical case in the literature to explore this association.